Fe@Fe2O3-loaded biochar as an efficient heterogeneous Fenton catalyst for organic pollutants removal. (7th May 2022) - Chen, Diwei; Zheng, Zhiyan; Zhang, Feiji; Ke, Rufu; Sun, Nan; Wang, Yonghao; Wang, Yongjing
Abstract: With increased demand for various chemical raw materials, sudden pollution incidents are more prone to occur during their transportation and usage, threatening the environment and human health. In this study, discarded tea stalks were recycled into composite materials (FSC-X00: X represents the calcination temperature) by impregnating tea stalks in Fe 2+ solution combined with subsequent calcination. X-ray diffractometer (XRD) and X-ray photoelectron spectroscopy (XPS) patterns verified the existence of Fe 0 and Fe2 O3, and Fe2 O3 was gradually reduced to Fe 0 when the calcination temperature was raised from 700 °C to 900 °C. FSC-X00 was adopted as a heterogeneous catalyst for activating H2 O2 to quickly degrade phenol in the water system. The degradation experiments indicated that FSC-600 exhibited superior degradation performance for phenol (20 mg/L) within 5 min and 80% total organic carbon (TOC) removal rate at pH = 3 within 30 min. The effects of the calcination temperature, the pH value and the amount of H2 O2 on the degradation efficiency were investigated. Competing experiments showed that fulvic acid (FA) and inorganic salts Na + had little effect on the degradation performance. The FSC-600 catalyst can be reused by thermal reduction. In addition, it was found that FSC-600 has a good degradation effect on ciprofloxacin (CIP), norfloxacin (NOR) and enrofloxacin (ENR), indicating that FSC-600 catalysts are a promising candidate for quick degradation of organic pollutants by Fenton reaction. Electron paramagnetic resonance (EPR) spectra analysis indicated that OH is the dominant reactive oxygen species (ROS) and part 1 O2 from O2 also participated in the degradation. This study provides an example of creating catalysts from organic solid waste for use in emergency treatment for phenol. HIGHLIGHTS: Fe@Fe2 O3 -loaded biochar (FSC-600) was prepared by waste tea stalks and FeSO4 combined with calcinations. FSC-600-H2 O2 exhibited superior degradation performance for phenol, ciprofloxacin, norfloxacin and enrofloxacin in a short period. Mechanism analysis indicates that OH is the dominant ROS and a little 1 O2 from O2 also participated the degradation. Graphical Abstract